How do people with disabilities in three regions of Guatemala make healthcare decisions? A qualitative study focusing on use of primary healthcare services - Goli Hashemi; Mary Wickenden; Ana Leticia Santos; Hannah Kuper (Public Library of Science (PLoS), 2023)
Research has demonstrated that persons with disabilities, despite their greater need for healthcare services, often experience greater barriers to accessing healthcare including primary healthcare. Data and interventions on access to primary healthcare for persons with disabilities to date appear to concentrate more on access and quality issues once the person with a disability has initiated the healthcare seeking process, with less emphasis on how healthcare decisions are made at the personal or household level when one identifies a healthcare need. The aim of this study was to investigate how healthcare decisions are made by people with disabilities when they first identify a healthcare need. It is anticipated that gaining a better understanding of how such decisions are made will facilitate the development of interventions and approaches to improve access to primary healthcare services for this group. A qualitative study was undertaken in Guatemala. In-depth interviews were undertaken with twenty-seven adults with disabilities, including men and women with a range of impairment types and ages. Data were analyzed using thematic analysis to identify themes that influence the decision-making processes in accessing primary healthcare services for people with disabilities. Thematic analysis of the interviews along with exploration of three existing access to health frameworks and models, led to identification of four primary themes and development of a new conceptual framework highlighting the complex decision-making process undertaken by people with disabilities about whether to seek primary healthcare services or not when confronted with a healthcare concern. The themes include perceived severity of illness and need for treatment, personal attributes, societal factors, and health system characteristics. Using this new conceptual framework will facilitate the development of more effective policies and interventions to improve access to primary healthcare services for people with disabilities through greater understanding of the complex network of variables and barriers.